Thrust/drag decomposition using partial pressure fields - Hart, Pierce L.; Mutangara, Ngonidzashe E.; Sanders, Drewan S.; Schmitz, Sven (Association Aeronautique et Astronautique de France (3AF), 2023)
The accurate prediction of aircraft performance requires a robust definition of thrust/drag accounting. Traditional nacelle-pylon configurations have been treated as separate entities which are combined linearly; however, this is not feasible for embedded propulsion systems which have a higher degree of interaction than traditional designs. With the apparent shift to embedded propulsion systems in the N+3 generation of aircraft, of which boundary layer ingestion technology is a driving factor, improving our understanding of propulsion system interactions with an air-frame has never been more important. Since many of these interactions occur close to the body, a near-field decomposition method, partial pressure fields, is employed in CFD to provide insight as to the interactive aerodynamics of an embedded propulsion system.
Presented at: 57th 3AF Applied Aerodynamics Conference AERO2023, 29-31 March 2023, Bordeaux, France